Review of electro-hydraulic hitch system control method of automated tractors - Wang, Ling; Wang, Yu; Dai, Dong; Wang, Xin; Wang, Shumao (International Journal of Agricultural and Biological Engineering, 2021)
The automatic and intelligent degree of tractor hitch system determines the operations quality, efficiency, tractor power output and energy consumption, and automatic control of electro-hydraulic hitch is one of the key technical problems in the realization of automated tractor. In this study, the adjustment methods and characteristics of electro-hydraulic hitch system were summarized. The development of electro-hydraulic hitch control technologies was elaborated and analyzed from both the electro-hydraulic control strategy and slip control strategy perspectives. The implementation methods and control characteristics were discussed. A new idea for the development of automated tractor was put forward that integrating cutting-edge technologies such as big data, fusion control and artificial intelligence. In addition, based on the precise and efficient control of electro-hydraulic hitch system, a high reliability of the control system of the tractor with intelligent application of the control algorithm was obtained. The results can provide a reference for the precise operation of automated tractors under the big data in agriculture.Keywords: automated tractors, electro-hydraulic hitch, control algorithm, draft-position control, slip rate controlDOI: 10.25165/j.ijabe.20211403.6175Citation: Wang L, Wang Y, Dai D, Wang X, Wang S M. Review of electro-hydraulic hitch system control method of automated tractors. Int J Agric & Biol Eng, 2021; 14(3): 1–11.